The implementation of systematic pain and sedation management has no impact on outcome in extremely preterm infants. (10th February 2016) - Deindl, Philipp; Giordano, Vito; Fuiko, Renate; Waldhoer, Thomas; Unterasinger, Lukas; Berger, Angelika; Olischar, Monika
Abstract: Aim: This study compared the short‐term and neurodevelopmental outcomes of extremely preterm infants before and after the implementation of a protocol to manage neonatal pain and sedation. Methods: Our study cohort comprised 140 extremely preterm infants from two neonatal intensive care units. We retrospectively analysed opiate exposure, time on mechanical ventilation, inotropic support, nutritional aspects and growth 12 months before (controls) vs 12 months after (intervention) the implementation of the Vienna Protocol for Neonatal Pain and Sedation. Infants were evaluated at the corrected age of 12 months using the Bayley Scales of Infant Development – Second Edition. Results: After the protocol was implemented, the cumulative opiate dose increased from a baseline of 15 mg/kg ± 41 to 89 mg/kg ± 228 morphine equivalents. Time on mechanical ventilation, inotropic support, length of parenteral nutrition, growth, length of stay and in‐hospital morbidity were similar before and after the implementation, with no differences between the groups in mental, motor and behavioural development at the one‐year follow‐up. However, opiate exposure was a possible risk factor for lower behaviour rating scores (estimate = −0.04; p = 0.006). [Correction added on 23 February 2016, after online publication: In the preceding sentences, the cumulative opiate dose as well as the estimate value for the behavioral rating scale were previously incorrect and have been amended in this current version.] Conclusion: Implementing a neonatal pain and sedation protocol increased opiate exposure, but had no effect on the in‐hospital and neurodevelopmental outcomes of extremely preterm infants. Abstract :